The Effect of Vegetable Waste Compost on The Growth of Robusta Coffee Seeds (Coffea canephora) - Mulyanti Mulyanti; Lukman Martunis; Ade Zahara (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Vegetable compost is an organic fertilizer derived from vegetable waste which can be used as a source of nutrients for plants. This study aims to determine the effect of vegetable waste compost on the growth of robusta coffee seedlings. This study used a non-factorial completely randomized design with 6 treatments and 4 replications to obtain 24 experimental units. The treatment given was a dose of vegetable waste compost consisting of 6 levels, namely: K0 = without adding vegetable waste compost K1 = 100 gram dose of vegetable waste compost, K2 = 200 gram dose of vegetable waste compost, K3 = 300 gram dose of vegetable waste compost, K4 = 400 gram dose of vegetable waste compost, K5 = 500 gram dose of vegetable waste compost. The results showed that the application of vegetable waste compost with different doses had a very significant effect on the parameters of seedling height, number of leaves and stem diameter of robusta coffee plant seedlings. The best treatment was obtained in the K5 treatment, namely 50 grams/plant of vegetable waste compost.